A Two-party certificateless authenticated key agreement protocol without pairing - Mengbo Hou; Qiuliang Xu (2009 2nd IEEE International Conference on Computer Science and Information Technology, 2009)
Authenticated key agreement (AK) protocol is crucial in providing data confidentiality and integrity for subsequent communications among two or more parties over a public network. Certificateless public key cryptography (CL-PKC) combines the advantage of the identity-based public key cryptography (ID-PKC) and the traditional public key cryptography (PKC). Unfortunately, construction of CL-PKC and AK protocols has so far depended on the use of identity-based encryption, which results in the bilinear pairing-based schemes that need costly operations. We present a secure certificateless authenticated key agreement protocol without paring, based on the certificateless encryption scheme proposed by J. Baek et al. It shows that the newly proposed scheme is of nice efficiency and practical. Moreover, it provides perfect forward secrecy, PKG forward secrecy and almost all the other known security attributes, such as known-key secrecy, key-compromise impersonation resilience, unknown key-share resilience, known session-specific temporary information security, message independence and no key control.